Issues of Capital Market Development in Uzbekistan - Ugli, Solijonov Muhammadaziz Shokirjon (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article deals with the development of the stock market and strengthening the capital market of the Republic of Uzbekistan, as well as the problems in this regard. On the basis of the results of the analysis, proposals were developed for the development of the stock market in Uzbekistan, organizational and institutional problems of the development of the capital market, the problem of transaction costs in the capital market, and personnel training.